2022
DOI: 10.3390/genes13122291
|View full text |Cite
|
Sign up to set email alerts
|

Complete Plastome of Physalis angulata var. villosa, Gene Organization, Comparative Genomics and Phylogenetic Relationships among Solanaceae

Abstract: Physalis angulata var. villosa, rich in withanolides, has been used as a traditional Chinese medicine for many years. To date, few extensive molecular studies of this plant have been conducted. In the present study, the plastome of P. angulata var. villosa was sequenced, characterized and compared with that of other Physalis species, and a phylogenetic analysis was conducted in the family Solanaceae. The plastome of P. angulata var. villosa was 156,898 bp in length with a GC content of 37.52%, and exhibited a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Genetic variations in G. mangostana cultivars have been shown by randomly amplified DNA fingerprinting (RAF) and inter simple sequence repeat (ISSR) molecular markers [ 58 , 59 , 60 ]. Plastomes also contain SSR and long repeats [ 61 , 62 , 63 , 64 ]. SSR, which is a stretch of 1–6 bp small repeats, is found extensively in different regions of the plastome, such as the intergenic regions, intron regions, and protein-coding regions [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations in G. mangostana cultivars have been shown by randomly amplified DNA fingerprinting (RAF) and inter simple sequence repeat (ISSR) molecular markers [ 58 , 59 , 60 ]. Plastomes also contain SSR and long repeats [ 61 , 62 , 63 , 64 ]. SSR, which is a stretch of 1–6 bp small repeats, is found extensively in different regions of the plastome, such as the intergenic regions, intron regions, and protein-coding regions [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…villosa Bonati, P. alkekengi , P. minima , P. pubescens , P. peruviana , P. pruinosa , Physalis cordata Houst. ex Mill., P. philadelphica , Physalis macrophysa Rydb., and P. ixocarpa were available ( Sandoval-Padilla et al., 2019 ; Zamora-Tavares et al., 2019 ; Feng et al., 2020 ; Zhan et al., 2022 ; Sandoval-Padilla et al., 2022a , b ; Zhang et al., 2023 ) ( Table 3 ). The complete chloroplast genomes mentioned above ranged in size from 156,578 to 157,007 bp, with the number of protein coding genes ranging from 79 to 80 and the number of tRNA genes ranging from 30 to 31 ( Sandoval-Padilla et al., 2019 ; Zamora-Tavares et al., 2019 ; Feng et al., 2020 ; Sandoval-Padilla et al., 2022a , b ).…”
Section: Application Of Omics In Physalis Studymentioning
confidence: 99%
“…P. angulata has high potential medicinal value and a very long history of being used in traditional medicines around the world. Recent phytochemical and pharmacological studies have confirmed that P. angulata is rich in vitamins, minerals, antioxidants, and many important pharmacologically active constituents, including antibacterial, anti-inflammatory, and anticancer ingredients [3][4][5][6]. In many countries, such as China, Indonesia, Peru, Mexico, and Brazil, P. angulata is often used to treat a variety of illnesses, including dermatitis, tracheitis, impaludism, rheumatism, hepatitis, and analogous conditions [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, such as China, Indonesia, Peru, Mexico, and Brazil, P. angulata is often used to treat a variety of illnesses, including dermatitis, tracheitis, impaludism, rheumatism, hepatitis, and analogous conditions [7][8][9][10]. Recently, increasing attention has been paid to the phytochemical and pharmacological aspects of P. angulata, and a variety of bioactive steroids with antitumor activities, including physagulins (A−Q), physangulidines (A−C), withangulatins (A−I), physalins (B, D, F−H), and withaminimin, have been isolated from the species [4,5,11]. Due to their important medicinal value, P. angulata plants have been widely cultivated in some regions of China for decades.…”
Section: Introductionmentioning
confidence: 99%